Tarian Keberuntungan yang Rumit: Mengurai Paradoks Nasib Buruk - Maulana, Muhammad Fadli Maulana; Azzahra, Filosophia Azzahra; Gunawan, Ayub Gunawan; Santoso, Gunawan (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this study is to find out the Nova Effect perspective from the Vnvlan youtube channel entitled